2014
DOI: 10.1146/annurev-psych-010213-115202
|View full text |Cite
|
Sign up to set email alerts
|

Is Adolescence a Sensitive Period for Sociocultural Processing?

Abstract: Adolescence is a period of formative biological and social transition. Social cognitive processes involved in navigating increasingly complex and intimate relationships continue to develop throughout adolescence. Here, we describe the functional and structural changes occurring in the brain during this period of life and how they relate to navigating the social environment. Areas of the social brain undergo both structural changes and functional reorganization during the second decade of life, possibly reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
1,203
11
45

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,511 publications
(1,300 citation statements)
references
References 124 publications
41
1,203
11
45
Order By: Relevance
“…This variable was taken as a mediator in processes, a variable involving changes in maturation and coping, and not merely a chronological variable. Looking at the average scores, it may be observed that in the later years of adolescence (mainly the study period from 17-21 years) sensitivity to peer evaluation (IR) diminished (Blakemore and Mills, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…This variable was taken as a mediator in processes, a variable involving changes in maturation and coping, and not merely a chronological variable. Looking at the average scores, it may be observed that in the later years of adolescence (mainly the study period from 17-21 years) sensitivity to peer evaluation (IR) diminished (Blakemore and Mills, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…It is clear from previous studies that peers affect adolescents' decisions to engage (or not engage) in risky behaviors (Blakemore and Mills 2014;Miller 2009). Social acceptance becomes central to much of adolescent behavior, perhaps because it is a developmentally sensitive period in which youth are highly attuned to picking up on and responding to social cues from their social environments (Blakemore and Mills 2014).…”
Section: Adolescence: a Time For Gender Salience And Peer Influencesmentioning
confidence: 99%
“…It is clear from previous studies that peers affect adolescents' decisions to engage (or not engage) in risky behaviors (Blakemore and Mills 2014;Miller 2009). Social acceptance becomes central to much of adolescent behavior, perhaps because it is a developmentally sensitive period in which youth are highly attuned to picking up on and responding to social cues from their social environments (Blakemore and Mills 2014). Thus, to the degree that social conformity is perceived as central to popularity among peers, early and middle adolescents are especially vulnerable to peer pressure as they strive toward peer approval and acceptance (Gavin and Furman 1989).…”
Section: Adolescence: a Time For Gender Salience And Peer Influencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescence is a key developmental time period for the emergence of psychosocial difficulties, and mental health disorders (Thapar et al 2012;Blakemore & Mills, 2014). To promote adaptive psychosocial functioning (PSF) during adolescence, appropriate conceptualisation and quantification of resilient functioning and its predictors is a crucial first step.…”
Section: Introductionmentioning
confidence: 99%